Making social media an instrument of democracy - Wischmeyer, Thomas (European law journal : review of European law in context, 2019)
In recent years, the responsibility of social media platforms towards their users and society at large has become a major political issue. However, the regulatory responses to the crisis of social media are still mostly considered unsatisfactory, as demonstrated by the widespread criticism of the German Network Enforcement Act of 2017. This article compares the current constitutional discourse on social media regulation with the debates that accompanied the last major transformation of the media landscape: the rise of broadcasting. While we certainly do not find a roadmap for social media regulation in the past, the key concept of the broadcasting discourse-the idea of media as a sphere of 'institutional freedom'-can be applied to the challenges of today and can be used to strengthen the democratic function of social media.